Komparasi Algoritma Suport Vector Machine Dan Naive Bayes Dalam Analisis Sentimen Kebijakan PPKM - Rico Pramestiawan (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2022)
Corona virus is an infectious disease that attacks human respiration. This virus originated in China, more precisely in Wuhan City, Hubei Province. early March 2020 this virus entered Indonesia and has spread throughout the world. In Indonesia there are 6,721,095 people exposed to Covid-19 and 160,648 people have died. This makes the government quickly make policies, in a policy there will be pros and cons in the community, so that sentiment analysis is needed to find out the response of the community regarding policies issued by the government, in this case the policy on the Implementation of PPKM.Keywords: Suport Vector Machine algorithm and Naïve Bayes algorithm; Rapid Miner;